ELABORASI MEDIA PEMBELAJARAN INTERAKTIF E-MODUL BERBASIS PROJECT BASED LEARNING BAGI GURU AQIDAH AKHLAK DI MTSN 16 JOMBANG - Niswah Qonita; Muhamad Khoirur Roziqin; Khoirun Nisa’ (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to develop an interactive e-module based on Project-Based Learning (PjBL) for the Aqidah Akhlaq subject and to determine the extent to which the e-module is suitable for use, as well as students’ responses to its implementation in the learning process. This study employs a Research and Development (R&D) approach using the ADDIE model, which consists of five steps: analyze, design, develop, implement, and evaluate. The research subjects included the Aqidah Akhlaq subject teacher, seventh-grade students at MTsN 16 Jombang, and two validators who served as subject matter experts and media experts. Data collection techniques involved observation, interviews, questionnaire completion, and review of relevant documents. The data were analyzed using quantitative and qualitative approaches with descriptive statistical methods and a paired-sample t-test. The results of this study indicate that the PjBL-based interactive e-module is deemed suitable for use. This is based on the validation results from the content expert, who rated its suitability at 87.8% falling into the “highly suitable” category and the validation from the media expert, which reached 83.33% falling into the “suitable” category. The use of e-modules demonstrated an improvement in student learning outcomes, with an average pretest score of 68.42 and a posttest score of 82.63. Statistical tests revealed a significant difference (p < 0.05), indicating that the e-modules successfully enhanced students’ understanding of the Virtues of Good Character curriculum. Additionally, student feedback on the use of the e-module reached 84.21% in the “highly satisfactory” category. Based on these findings, it can be concluded that interactive e-modules based on Project-Based Learning are highly suitable and effective as a teaching tool for Aqidah Akhlak in junior high schools. This e-module can tangibly enhance student engagement, motivation to learn, and understanding of moral values, which can be applied in daily life. This study is expected to serve as a reference for developing digital learning media in the field of Islamic religious education.